Trend of clients attending an integrated councelling and testing centre of a tertiary care hospital in North Karnataka: a record based study - Nayak, Rakesh K.; Kulkarni, Raghavendra D.; Ajantha, Ganavalli S. (International Journal Of Community Medicine And Public Health, 2019)
Background: The prevalence of HIV among the adult population has continued a steady decline at the national level from an estimated peak of 0.4% in 2000 down to 0.26% in 2015. The data generated by ICTC may provide important clues to understand the epidemiology of the disease in a specific area, as well as pattern of risk behavior of the population. Methods: The present retrospective record based cross sectional study was carried out at the ICTC Centre of SDM College of Medical Sciences and Hospital, Dharwad. Retrospective data for the past six years (2012-13 to 2017-18) on clients visiting the ICTC was collected from the ICTC registers. Results: A total of 45,066 clients attended the ICTC over a period of 6 years, among which 61.6% were females and 38.4% were males. Among the total females, 55% were antenatal mothers. Out of the total clients tested, 99.75% of clients underwent post-test counseling. Among the total clients, 669 were HIV sero-positive clients out of which majority (61.7%) were males. The total positivity rate was 1.48% among the ICTC attendees. 47 clients had co-infections with TB. Conclusions: The challenge is to increase access to and uptake of HIV testing priority. Intense IEC activities for behaviour change at grass root level populations should be encouraged.